Mewujudkan Perpustakaan Ideal menuju pada Peningkatan Mutu Pendidikan di Perguruan Tinggi - UH, Irma Rumtianing (Pustakaloka, 2009)
Spirit and reverberation to enhance significant library role for educational institution recently become more perceptible because our country nowadays is left behind by other neighboring contries in this matter. The agenda to reformn education keeps on and the improvement of library based education is discoursed continually.